2011
DOI: 10.1051/0004-6361/201015587
|View full text |Cite
|
Sign up to set email alerts
|

Photospheric and coronal abundances in solar-type stars: the peculiar case ofτ Bootis

Abstract: Aims. Chemical abundances in solar-type stars are still a much debated topic in many respects. In particular, planet-hosting stars are known to be metal-rich, but whether or not this peculiarity applies also to the chemical composition of the outer stellar atmospheres is still to be clarified. More in general, coronal and photospheric abundances in late-type stars appear to be different in many cases, but understanding how chemical stratification effects work in stellar atmospheres requires an observational ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 44 publications
6
21
0
Order By: Relevance
“…While we have modelled the stellar wind that flows along the large‐scale coronal magnetic field lines, the environment surrounding a star is likely to be much more dynamic, especially for a star such as τ Boo that is more active than the Sun (Maggio et al 2011). We note that the radio flux estimated here is expected to increase if the planet is hit by powerful ejections of coronal material, e.g.…”
Section: Results: Radio Emission From Wind–planet Interactionmentioning
confidence: 99%
“…While we have modelled the stellar wind that flows along the large‐scale coronal magnetic field lines, the environment surrounding a star is likely to be much more dynamic, especially for a star such as τ Boo that is more active than the Sun (Maggio et al 2011). We note that the radio flux estimated here is expected to increase if the planet is hit by powerful ejections of coronal material, e.g.…”
Section: Results: Radio Emission From Wind–planet Interactionmentioning
confidence: 99%
“…For τ Boo A and π 1 UMa the solution is to simply use published [Fe/H] measurements from XMM (Telleschi et al 2005;Maggio et al 2011). Observations from XMM are well suited for continuum measurement, with the high sensitivity of RGS and the possibility of considering spectra from both RGS and from the EPIC instrument.…”
Section: Coronal Abundance Meaurementsmentioning
confidence: 99%
“…The coronal abundances of τ Boo and α Cen A, B were extensively analyzed by Maggio et al (2011) and by Raassen et al (2003) respectively. Maggio et al (2011) found a flat FIP dependence, while Raassen et al (2003) measured a solar-like FIP behavior.…”
Section: Object Selectionmentioning
confidence: 99%
“…Maggio et al (2011) analyzed the FIP behavior of this object. No clear FIP (or IFIP) trend was observed.…”
Section: τ Boomentioning
confidence: 99%
See 1 more Smart Citation